Complete Covalent Structure of Human Platelet Factor 4 - Morgan, Francis J; Begg, Geoffrey S; Chesterman, Colin N (Thrombosis and Haemostasis, 1979)
The amino acid sequence of the subunit of human platelet factor 4 has been determined. Human platelet factor 4 consists of identical subunits containing 70 amino acids, each with a molecular weight of 7,756. The molecule contains no methionine, phenylalanine or tryptophan. The proposed amino acid sequence of PF4 is: Glu-Ala-Glu-Glu-Asp-Gly-Asp-Leu-Gln-Cys-Leu-Cys-Val-Lys-Thr-Thr-Ser- Gln-Val-Arg-Pro-Arg-His-Ile-Thr-Ser-Leu-Glu-Val-Ile-Lys-Ala-Gly-Pro-His-Cys-Pro-Thr-Ala-Gin- Leu-Ile-Ala-Thr-Leu-Lys-Asn-Gly-Arg-Lys-Ile-Cys-Leu-Asp-Leu-Gln-Ala-Pro-Leu-Tyr-Lys-Lys- Ile-Ile-Lys-Lys-Leu-Leu-Glu-Ser. From consideration of the homology with p-thromboglobulin, disulphide bonds between residues 10 and 36 and between residues 12 and 52 can be inferred.